Intergenerational Progress of Mexican-Origin Workers in the U.S. Labor Market - Stephen J. Trejo (Institute for the Study of Labor (IZA), 2001)
Using unique Current Population Survey data from November 1979 and 1989, this paper compares the wage structure across generations of Mexican-origin men. I find that the sizable earnings advantage U.S.-born Mexican Americans enjoy over Mexican immigrants arises not just from intergenerational improvements in years of schooling and English proficiency, but also from increased returns to human capital for Mexican-origin workers who were born and educated in the United States. Even if we consider immigrants who have worked in the United States for 40 years and who therefore have had ample time for labor market assimilation, my estimates indicate that a discrete jump in earnings and the wage structure occurs between the first and second generations. Progress seems to stall after the second generation, however, as the much more modest gains in schooling and English fluency that occur between the second and third generations do not appear to raise the earnings of Mexican Americans any further.
Keywords: J61; J31; J15; 330; Mexican; wages; intergenerational; Migranten; Lohn; Mexikaner; Generationenbeziehungen; Soziale Integration; Bildungsertrag; Schätzung; USA